Heat Injury in Open-Water Swimming: A Narrative Review. Issue 4 (April 2021) - Murphy, Micheal; Polston, Keith; Carroll, Michael; Alm, John
Abstract : Abstract: Swimming is one of the most popular sports in the world with open-water swimming (OWS) gaining more and more prominence since being featured in the Federation Internationale De Natation World Aquatics Championships in 1992 and the Olympic Games in 2000. The aim of this review is to analyze the existing literature on heat injury in OWS. Relevant literature was located via computer-generated citations during November of 2020 through online computer searches of multiple major databases. Athletes participating in OWS are exposed to environmental conditions that place them at risk for unique medical conditions such as heat injury. Clinicians providing care for OWS athletes should be educated and trained to recognize these conditions and minimize risks to optimize athlete safety. This article identifies medical challenges related to heat injury in OWS while investigating water temperature recommendations, physiological effects of hyperthermia, risk mitigation strategies, and treatment measures. Abstract : Open-water swimming athletes may be at increased risk for heat-related injury, which necessitates attention from practitioners to ensure athlete safety.